Enantioselective analysis of ibuprofen, ketoprofen and naproxen in wastewater and environmental water samples - Hashim, Nor H.; Stuart J. Khan, Stuart J. Khan (Elsevier, 2011)
A highly sensitive and reliable method for the enantioselective analysis of ibuprofen, ketoprofen and naproxen in wastewater and environmental water samples has been developed. These three pharmaceuticals are chiral molecules and the variable presence of their individual (R)- and (S)-enantiomers is of increasing interestfor environmental analysis. An indirect method for enantioseparation was achieved by the derivatization of the (R)- and (S)-enantiomers to amide diastereomers using (R)-1-phenylethylamine ((R)-1-PEA). After initial solid phase extraction from aqueous samples, derivatization was undertaken at room temperature in less than 5 min. Optimum recovery and clean-up of the amide diastereomers from the derivatization solution was achieved by a second solid phase extraction step. Separation and detection ofthe individual diastereomers was undertaken by gas chromatography–tandem mass spectrometry (GC–MS/MS). Excellent analyte separation and peak shapes were achieved for the derivatized (R)- and (S)-enantiomers for all three pharmaceuticals with peak resolution, Rs is in the range of 2.87–4.02 for all diastereomer pairs. Furthermore, the calibration curves developed for the (S)-enantiomers revealed excellent linearity (r2 ≥ 0.99) for all three compounds. Method detection limits were shown to be within the range of 0.2–3.3 ng L−1 for individual enantiomers in ultrapure water, drinking water, surface water and a synthetic wastewater. Finally, the method was shown to perform well on a real tertiary treated wastewater sample, revealing measurable concentrations of both (R)- and (S)-enantiomers of ibuprofen, naproxen and ketoprofen. Isotope dilution using racemic D3-ibuprofen, racemic D3-ketoprofen and racemic D3-naproxen was shown to be an essential aspect of this method for accurate quantification and enantiomeric fraction (EF) determination. This approach produced excellent reproducibility for EF determination of triplicate tertiary treated wastewater samples.